Seasonality in pain, sleep and mental distress in patients with chronic musculoskeletal pain at latitude 69° N. (1st November 2020) - Abeler, Karin; Sand, Trond; Friborg, Oddgeir; Bergvik, Svein
ABSTRACT: Seasonality is evident in several aspects of human health and behavior, whereas seasonality in chronic pain is less well studied. We examined seasonal variation in pain severity and pain dissemination, as well as in pain-associated conditions, such as sleep impairment, sleep timing, mental distress, fatigue and physical activity. We also examined if any of these associated conditions moderated the seasonality in pain. This prospective study was conducted in the subarctic municipality of Tromsø, Norway (69º North), on a sample of patients with chronic musculoskeletal pain ( N = 56). Data were collected with self-report questionnaires and objective actigraphy measures (7 days) twice: winter and summer. Mixed linear regression models were fitted. A modest seasonality effect was observed in pain severity (highest in summer), but not in pain dissemination. Seasonality with increased physical activity and delayed sleep timing in the summer was also present. The remaining pain-associated self-report or objective measures indicated no seasonality. The season–pain association was not significantly moderated by any of the pain-associated conditions. Previous studies on healthy individuals residing in polar areas have suggested an opposite seasonal effect with delay of the sleep–wake rhythm in winter. Our results based on a clinical sample thus represent a novel finding that needs to be examined further with regard to seasonal circadian entrainment and alignment in pain populations. These results may have clinical value for the treatment of patients with musculoskeletal pain as seasonality may require seasonal adjustments of pain treatment strategies.